LIMNOLOGY AND TROPHIC STATUS OF SHAHPUR DAM RESERVOIR, PAKISTAN - M. Y. Janjua; T. Ahmad; N. Akhtar (Journal of Animal and Plant Sciences, 2009)
Phytoplankton, because of their role as primary producers in an aquatic ecosystem are the subject of great interest and their qualitative and quantitative estimates can provide good indices of quality and productive capacity of water. Present studies were carried out to determine the seasonal phytoplankton composition and reservoir productivity of Shahpur Dam in Pakistan. Carlson Trophic Index was determined to analyze trophic status of reservoir. A total of 35 genera, belonging to 28 families and 7 classes were identified during the study. Class Chlorophyceae and Cyanobacteria were found to be most diverse and dominant. It was observed that Morpho-edaphic Index on TDS and Secchi depth were significantly correlated with chlorophyll-a concentration. Chlorophyll-a probably would be better indicator of trophic state of reservoir and in absence of chlorophyll-a data, MEI could be used as practical potential tool for fisheries management.
Keywords: Carlson’s TSI; chlorophyll a; phytoplankton; reservoirs; Pakistan